THU0434 Pharmacodynamic effects and safety of verinurad (RDEA3170) in combination with febuxostat versus febuxostat alone in adults with gout: a phase 2a, open-label study. (15th June 2017) - Fleischmann, R; Winkle, P; Hall, J; Valdez, S; Liu, S; Yan, X; Hicks, L; Hernandez-Illas, M
Abstract : Background: Verinurad (RDEA3170) is a high-affinity, selective URAT1 inhibitor in development for the treatment of gout and asymptomatic hyperuricemia. Objectives: This Phase 2a, randomized, open-label, multicenter study investigated the multiple-dose pharmacodynamics (PD), pharmacokinetics (PK), and safety of oral verinurad in combination with febuxostat versus febuxostat alone in adults with gout (NCT02246673 ). Methods: Patients aged ≥18 and ≤75 years with gout and serum uric acid (sUA) ≥8 mg/dL were randomized to 1 of 5 cohorts to receive febuxostat (40 mg and 80 mg) alone and in combination with verinurad (dose range 2.5 mg to 20 mg; 4 treatment periods per cohort, each treatment period 7 days). Medications were administered once daily ∼30 min after breakfast. Colchicine 0.6 mg for gout flare prophylaxis was initiated at approximately Day -14 (start of urate-lowering therapy [ULT]) washout) or Day -7 if not on ULT. Serial blood and urine samples were measured at preset intervals on Days -1, 1, 7, 14, 21, and 28 for PD and PK endpoints. Safety assessments included adverse events (AEs) and laboratory, electrocardiograms, and vital sign parameters. Results: Sixty-four patients were randomized (n=12–14 per cohort). Serum PD data pooled across cohorts demonstrated maximal % decrease in sUA from baseline (Emax) at 8–12 h after dosing. Addition of verinurad to febuxostat decreased sUA in dose-dependent manner (Figure 1 ). Greater sUA reductions were observed for dose combinations of verinurad ≥5 mg with febuxostat 40 mg versus febuxostat 80 mg alone. The rate of urinary uric acid excretion was reduced by febuxostat alone, but comparable to baseline levels with verinurad combined with febuxostat. Verinurad plasma exposures increased with verinurad dose and were comparable for febuxostat 40 mg and 80 mg doses. No drug-drug interaction on verinurad and febuxostat plasma PK parameters was observed. Verinurad at doses from 2.5 mg to 20 mg was well tolerated, with no serious AEs, withdrawals due to AEs, or renal-related events. The most frequent treatment-emergent AE possibly related to study medication was pain in extremity, in 2 patients receiving verinurad. Laboratory values and vital signs showed no clinically meaningful changes. There were no cases of serum creatinine elevation ≥1.5x baseline. Conclusions: Verinurad coadministered with febuxostat dose-dependently decreased sUA while maintaining urine uric acid levels comparable to baseline. All dose combinations of verinurad and febuxostat in this study were generally well tolerated with no serious AEs or renal-related events during combination treatment. Disclosure of Interest: R. Fleischmann Grant/research support from: Ardea Biosiences, Inc, P. Winkle Employee of: Anaheim Clinical Trials, J. Hall Employee of: Ardea Biosiences, Inc., S. Valdez Employee of: Ardea Biosiences, Inc., S. Liu Employee of: Ardea Biosiences, Inc., X. Yan Employee of: Ardea Biosiences, Inc., L. Hicks Employee of: Ardea Biosiences, Inc., M. Hernandez-Illas: None declared